A Study on Volunteer Motivation and Satisfaction in Malaysia's Sports Events - Ayu Rohaidah Ghazali; Nurakmal Ramli; Norol Hamiza Zamzuri; Norhidayah Mohd Rashid; Abdul Hamid Abdul Halim; Nor Azzura Nordin (Information Management and Business Review, 2024)
Despite the critical role of volunteers in the success of sports events, there is limited research in Malaysia on how volunteer motivations and experiences impact their satisfaction. This research sets out to examine the vital position played by volunteers in ensuring successful sports events, with emphasis on volunteer motivation, experience and satisfaction among undergraduates and postgraduate students at a local Malaysian university. The study utilizes quantitative analysis where significant correlations between these variables were discovered revealing that volunteer motivation and positive event experiences are important to enhancing volunteer satisfaction. Data from eighty students (80) showed that event-related factors such as the opportunity to be part of a prestige event and witness behind-the-scenes activities a significant motivators and key drivers of voluntary participation. The findings indicate that there was a significant beta coefficient supporting event-related motivation and volunteer experience towards volunteer satisfaction while purposive volunteer motivation did not gain significance. Overall, the research underscores the necessity for event planners to prioritize volunteer satisfaction by understanding and addressing their motivations and experiences, ultimately contributing to more meaningful and successful events.